2021
DOI: 10.1097/moh.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Casting a NET on cancer: the multiple roles for neutrophil extracellular traps in cancer

Abstract: Purpose of reviewThe role of the innate immune system has become widely appreciated in cancer and cancer-associated disorders. Neutrophils, the most abundant circulating leukocytes, have prognostic value in determining cancer progression and survival. One of the ways by which neutrophils negatively impact outcome is by formation of neutrophil extracellular traps (NETs) which result in release of nuclear chromatin and bioactive proteins into the extracellular space. Here, we review the evidence for NETs contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…Apart from a potential diagnostic value in DCI detection, NETs might serve as therapeutic targets. DNase or janus kinase inhibitors in humans and neonatal NET inhibitory factor in mice have shown promise to reduce NET formation and NET-mediated ischemic injury ( 32 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a potential diagnostic value in DCI detection, NETs might serve as therapeutic targets. DNase or janus kinase inhibitors in humans and neonatal NET inhibitory factor in mice have shown promise to reduce NET formation and NET-mediated ischemic injury ( 32 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting polyanions (cfDNA from NETs or other origin, polyphosphate and GAGs) in arterial, venous, infection-associated and cancer-associated thrombosis will remain a promising therapeutic approach with the hope of developing antithrombotics that do not interfere with physiological hemostasis [40 ▪▪ ,41,42 ▪▪ ,43 ▪ ]. Exploration of appropriate tools to eliminate the harmful effects of cfDNA and polyphosphates, or construction of a polyanion of optimal size and charge to confer potent histone-neutralizing properties would be of great clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The exposed phosphatidylserine on TF-positive EVs appears to promote the binding of coagulation factors, rather than TF. NETs serve as a scaffold for various procoagulants and act as mediators of CAT ( 149 ). It has been shown that 4T1-derived exosome range EVs induce NET formation in the neutrophils of granulocyte colony-stimulating factor-treated mice ( 150 ).…”
Section: Roles Of Pcsk9 In Thrombosis and Haemostasis Under Disease S...mentioning
confidence: 99%